Pengaruh Iklan Televisi terhadap Brand Awareness Shopee Di PT. Shopee International Indonesia Jakarta - Nurdina Shahab (Journal of Economics and Business UBS, 2019)
This study aims to determine whether there is an influence of Shopee television advertising on Shopee brand awareness at PT. Shopee International Indonesia Jakarta. This research was conducted in July 2018 through the help of Google Form (online questionnaire). The population in this study is Shopee consumers in TB Simatupang office area. Sampling using purposive sampling technique. Research data was obtained through an online questionnaire about television advertising and brand awareness for 100 respondents. The instrument testing method used is testing validity and reliability. Data analysis techniques used are quantitative descriptive techniques, simple linear regression analysis and t test. The results showed that in television advertising has an influence on Shopee brand awareness.